Connecting families: a qualitative study examining the experiences of parenting young children under financial strain in Ontario, Canada - Mary I. Martin; Dane Mauer-Vakil; Cornelia M. Borkhoff; Patricia C. Parkin; Imaan Bayoumi (BMC, 2024)
Abstract Background There is little research investigating the subjective experiences of parenting young children while living in poverty and experiencing financial strain using qualitative methodologies. Therefore, the objective of this study was to employ a qualitative approach to provide a nuanced and balanced view on the topic of parenting young children under financial strain in the Canadian context. Methods We conducted a qualitative study using semi-structured interviews between July and August 2021 in Kingston, Ontario, Canada. Sixteen participants aged 20-39 self-identified as living under financial strain while parenting a child aged 2-5 years. A qualitative inductive thematic analysis was undertaken with a focus on describing the contents of the data. Results Four major themes emerged from the data: experience of being a parent, impact of financial strain on the family unit, impact of financial strain on the children, and impact of financial strain on the parent. Numerous deleterious physical, mental, and material impacts on the family unit and parent were identified, however parent-perceived impacts of financial strain on their children were minimal. Parents described striking levels of resourcefulness and resiliency in providing the necessities for their families, absorbing the most significant impacts of financial strain through the phenomenon of self-sacrifice. Conclusion The impacts of financial strain on families with young children are far reaching. Further research into the impacts of self-sacrifice on parents experiencing financial strain are needed to better understand this issue, and to inform social programming and resources that could help alleviate the deleterious impacts of poverty on parent mental, social, and physical health.